RANCANG BANGUN SIMULASI PALANG KERETA API OTOMATIS MENGGUNAKAN INFRARED GP2Y0A02YK0F - David Boy Tonara; Yuwono Marta Dinata (SENTIA 2016, 2016)
The train is one mode of public transport that become the foundation of many people in Indonesia. In 2015 it is estimated this mode of transportation will transport 338 million passengers. With a passenger volume per schedule which is much higher than public transportation bus or plane, train safety side is the side that is very vital because it deals with the safety of many lives. This study will establish a system of automatic train doorstop that is expected to reduce the risk of accidents on the railways. Not just calculating the distance, the system automatically latch built railway will take into account the speed. Doorstop train system automatically on this research will be built based on Arduino controller. To calculate the speed and acceleration of the train, the train system automatically latch will use two infrared sensors. Where two of these sensors will be used to calculate the speed of the train.